2022
DOI: 10.1136/bmjopen-2022-061964
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of introducing a non-clinical community health advice and navigation service on the demand for primary care in socially deprived areas? Evidence from an observational panel study with difference-in-differences design

Abstract: ObjectivesTo examine the effect of introducing a non-clinical community health advice and navigation service on the demand for primary care in a socially deprived area.DesignObservational panel study with difference-in-differences design. We conducted fixed-effects negative binomial regressions to compare changes in the number of visits to general practitioners (GPs) in individuals who visited the health advice and navigation service and a matched control group of individuals who did not visit the service. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In one intervention in England, community health workers supported primary health care teams in a deprived urban area by addressing primarily social problems; this was associated with a reduction in the number of GP consultations and generally more appropriate use of primary care services (Abbott and Davidson, 2000). An earlier study of the same non‐clinical community health advice and navigation service examined in the present investigation found that this easily accessible first point of contact might improve access to the health system, reduce unmet care needs and increase demand (Wild et al., 2022). In this separate study, which aimed to assess the effect of the integrated care initiative on the demand for GP visits, the role of the cross‐sector network of providers was not considered.…”
Section: Literature Reviewmentioning
confidence: 77%
“…In one intervention in England, community health workers supported primary health care teams in a deprived urban area by addressing primarily social problems; this was associated with a reduction in the number of GP consultations and generally more appropriate use of primary care services (Abbott and Davidson, 2000). An earlier study of the same non‐clinical community health advice and navigation service examined in the present investigation found that this easily accessible first point of contact might improve access to the health system, reduce unmet care needs and increase demand (Wild et al., 2022). In this separate study, which aimed to assess the effect of the integrated care initiative on the demand for GP visits, the role of the cross‐sector network of providers was not considered.…”
Section: Literature Reviewmentioning
confidence: 77%